MiRNAs and ovarian cancer: a miRiad of mechanisms to induce cisplatin drug resistance. Issue 1 (2nd January 2016) - Samuel, Priya; Pink, Ryan Charles; Brooks, Susan Ann; Carter, David RaulFrancisco
Abstract : Ovarian cancer is the most aggressive gynecological cancer. One reason for the low 5-year survival rate of under 40% is that ovarian tumors usually acquire resistance to the platinum-based compounds used to treat them. Resistance to one such compound, cisplatin, can arise via numerous mechanisms that can be categorized as pre-, post-, on- or off-target. Pre-target mechanisms prevent accumulation of cisplatin in the cell, on-target mechanisms allow DNA damage to be repaired more efficiently, post-target mechanisms prevent the damage from inducing apoptosis and off-target mechanisms increase resistance via unrelated compensatory mechanisms. miRNAs are short non-coding RNAs that influence cellular function by repressing gene expression. Here we describe how miRNAs can induce cisplatin resistance in ovarian cancer cells via pre-, post-, on- and off-target mechanisms. A better understanding of how miRNAs feed into the mechanisms of drug resistance will inform the rational design of combination therapies for ovarian cancer.